2012
DOI: 10.2478/v10046-011-0043-z
|View full text |Cite
|
Sign up to set email alerts
|

Variation of spring barley agronomic traits significant for adaption to climate change in latvian breeding programmes

Abstract: Variation of spring barley agronomic traits significant for adaption to climate change in latvian breeding programmes Breeding programmes have been recently challenged by climate change. Spring barley (Hordeum vulgare L.) yield, phenological traits (days to heading, length of filling period and days to maturity) and resistance to powdery mildew and net blotch, which are influenced by the rising temperature and precipitation, along with threshability in hulless, were evaluated and their genetic and envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…Grain yield and quality traits of spring barley can vary greatly due to growing conditions (Leistrumaite and Paplauskiene, 2005). In a previous study, also at Stende, a significant effect of year on variation of yield of HB genotypes was also observed (Bleidere et al, 2012). Overall in this current study, grain yield, TGW, TW, starch and b-glucans in 2011 were significantly lower than in 2012.…”
Section: Discussionsupporting
confidence: 74%
“…Grain yield and quality traits of spring barley can vary greatly due to growing conditions (Leistrumaite and Paplauskiene, 2005). In a previous study, also at Stende, a significant effect of year on variation of yield of HB genotypes was also observed (Bleidere et al, 2012). Overall in this current study, grain yield, TGW, TW, starch and b-glucans in 2011 were significantly lower than in 2012.…”
Section: Discussionsupporting
confidence: 74%
“…significant difference between different years within the same trial sites for the NGS trait (Table 2). Bleidere et al [38] and Dofing et al [39] studying advanced bred cultivars of spring barley reported similar results in their studies showing significant interactions for environment x cultivar in different climatic conditions. One of the reasons for the environmental effect between Kyrgyzstan and Latvia is that there are differences in day lengths.…”
Section: Analysis Of Datasupporting
confidence: 56%
“…Leistrumaite and Paplauskiene (2005) found that the grain yield and quality traits of spring barley varieties vary greatly due to growing conditions. Significant effect of year as a factor to HB grain yield was observed in previous research carried out at Stende (Bleidere et al, 2012). Bleidere et al, (2013) found significant influence of genotype and nitrogen supply to the HB yield and quality characteristics.…”
Section: Discussionmentioning
confidence: 69%